Prevalence, Causes And Possible Remedies To The Incessant Collapse Of Buildings In Kenya. A Strategic Discourse - Paul, Wambua; Ogembo, John Otieno (Advances in Social Sciences Research Journal, 2018)
The study aimed at establishing the prevalence, causes and possible remedies to the incessant collapse of buildings in major urban centres in Kenya. In particular, the contribution of substandard building materials, poor workmanship and noncompliance to housing policy to the collapse of buildings were probed. Data was obtained from a convenient sample of 173 professionals in the housing industry. They included Architects, Valuers, Structural Engineers, Quantity Surveyors and Building Surveyors. Land Surveyors, Developers, Contractors, Planners and Estate agents were also involved in the study. Respondents were drawn from the public sector including Ministry of Lands and Housing, Regulatory Authorities, Professional Associations as well as practitioners in private practice. They completed a self report questionnaire with highly reliable six test variables (α=.772 to .966). Results showed that prevalence of collapse of buildings within the country is high consistent. Substandard building materials, poor workmanship and noncompliance to housing policy were the main causes of the collapse, noncompliance to housing policy contributing the greatest followed by substandard building materials and lastly poor workmanship. When adopted, organization control strategy partially mediated the relationship between the causes and the performance of the industry. It was shown to have the potential to reduce the influence of substandard building materials, poor workmanship and noncompliance to housing policy and thus spur the performance of the housing sector. The study therefore recommends structured adoption of organizational control strategy to help mitigate incessant collapse of buildings and ultimately enhance the performance of the housing industry within the country.